Chomp - Hiaasen, Carl. (Alfred A. Knopf, 2012)
When the difficult star of the reality television show "Expedition Survival" disappears while filming an episode in the Florida Everglades using animals from the wildlife refuge run by Wahoo Crane's family, Wahoo and classmate Tuna Gordon set out to find him while avoiding Tuna's gun-happy father.